Predicting behavior of AP-1000 nuclear reactor fuel rod under steady state operating condition by using FRAPCON-4.0 software - Nguyen, Trong Hung; Nguyen, Van Tung; Nguyen, Thanh Thuy; Cao, Duy Minh (Nuclear Science and Technology, 2018)
This paper reports the results on the predictions of behavior of AP-1000 nuclear reactor fuel rod under steady state operating condition by using FRAPCON-4.0 software. The predictive items were the temperature distribution in the fuel rod, including fuel centerline temperature, fuel pellet surface temperature, gas temperature, cladding inside and outside temperature, oxide surface and bulk coolant temperature; and gap conductance and thickness.The predictive items also include deformation of fuel pellets, fission gas release and rod internal pressure, cladding oxidation and hydration. The predictive data were suggested the fuel rod behavior image in nuclear reactor.